Digital Innovation for Quality Assurance in Higher Education: A Bibliometric Insight Over a Decade - Desty Hapsari Kirana; Kurnia Khafidhatur Rafiah (CV Putra Publisher, 2026)
This study aims to map the development of research on digital innovation in higher education quality assurance during 2015–2025 through a bibliometric analysis of 556 Scopus-indexed articles. The results show a significant increase in publications, especially since the COVID-19 pandemic, with a shift in focus from basic digitalization to the integration of intelligent technologies such as artificial intelligence and digital assessment in quality assurance systems. Keyword visualization reveals six main thematic clusters: higher education, COVID-19, e-learning, digitalization, digital transformation, and artificial intelligence. Citation analysis shows that the most influential literature highlights institutional digital transformation, technological readiness, online learning quality, and data-driven QA frameworks. These findings provide a comprehensive overview of the conceptual evolution and strategic challenges in strengthening digital-based quality assurance systems in higher education.